1995
DOI: 10.1152/ajpcell.1995.268.4.c925
|View full text |Cite
|
Sign up to set email alerts
|

Signaling and growth responses of LLC-PK1/Cl4 cells transfected with the rabbit AT1 ANG II receptor

Abstract: Angiotensin II (ANG II) receptors of the AT1 subtype are present on the apical and basolateral membranes of renal proximal tubule cells. Cells of the proximal tubulelike cell line, LLC-PK1/Cl4, were transfected with an expression plasmid containing cDNA encoding the rabbit AT1 ANG II receptor. In transfected cells, specific binding of 125I-ANG II was detected on both apical and basolateral membranes; wild-type LLC-PK1/Cl4 cells did not express ANG II receptors. In transfected cells, apical or basolateral ANG I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Growth factors such as Ang II have been implicated in development of renal cell hypertrophy through activation of AT1R (21,33). We previously reported that AT1R-transfected LLCPKcl4 cells do not increase DNA synthesis but increase protein synthesis in response to Ang II, as indicated by increased [ 3 H]leucine incorporation without increases in [ 3 H]thymidine incorporation (21).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Growth factors such as Ang II have been implicated in development of renal cell hypertrophy through activation of AT1R (21,33). We previously reported that AT1R-transfected LLCPKcl4 cells do not increase DNA synthesis but increase protein synthesis in response to Ang II, as indicated by increased [ 3 H]leucine incorporation without increases in [ 3 H]thymidine incorporation (21).…”
Section: Discussionmentioning
confidence: 96%
“…We previously reported that AT1R-transfected LLCPKcl4 cells do not increase DNA synthesis but increase protein synthesis in response to Ang II, as indicated by increased [ 3 H]leucine incorporation without increases in [ 3 H]thymidine incorporation (21). In rabbit proximal tubular cells and the rat kidney epithelial cell line NRK-52E, TGF-␤ converts EGF-induced hyperplasia into hypertrophy by inhibiting mitogen-induced hyperphosphorylation of pRB (the product of the retinoblastoma gene) (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that, despite normal or suppressed plasma renin activity, the intrarenal content of renin is increased in experimental diabetes models (Correa-Rotter et al, 1992;Jaffa et al, 1992;Burns and Harris, 1995;Carey and Siragy, 2003). Studies using Otsuka Long-Evans Tokushima Fatty rats, a model of type 2 diabetic nephropathy, showed increased activity of ACE in the kidney, although serum ACE activity was lower than that in control animals (Taniguchi et al, 2002).…”
Section: Angiotensin Ii-dependent Hypertensive Models a Angiotensinmentioning
confidence: 99%
“…LLC-PK 1 cells (Cl4) stably expressing the rabbit AT1 receptor were a kind gift from Dr. R. Harris (12). Cells were kept in DMEM containing 10% FBS, 100 U/ml penicillin, and 100 g/ml streptomycin in a humidified incubator at 37°C under 5% CO 2.…”
Section: Cellsmentioning
confidence: 99%